2017
DOI: 10.1016/j.jor.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spinal injuries on farms: Patients treated in the national spinal unit of Ireland 2005–2015

Abstract: The proximity to heavy machinery and livestock pose significant risk for spinal injuries. This study should encourage increased efforts to improve farm safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…All emergency presentations where "injury cause" had been recorded were included in the study. Injury cause included the following categories (code description): [1] Motor vehicle -driver, [2] Motor vehicle -passenger, [3] Motorcycle -driver, [4] Motorcycle -passenger, [5] Pedal cyclist -rider or passenger, [6] Pedestrian, [7] Horse related (fall from, struck or bitten by), [8] Other transportrelated circumstance, [9] Fall -low (same level or less than 1 metre, or no information on height), [10] Fallhigh (greater than 1 metre), [11] Submersion or drowning -swimming pool, [12] Submersion or drowning -other, [13] Other threat to breathing (includes strangulation and asphyxiation), [14] Fire, flames and smoke, [15] Scalds (hot drink, food, water, other fluid, steam, gas or vapour), [16] Contact burn (hot object or substance), [17] Poisoning -medication, [18] Poisoning -other or unspecified substance, [19] Firearm, [20] Cutting and piercing object, [21] Dog related, [22] Other animal related, [23] Struck by or collision with person, [24] Struck by or collision with object, [25] Machinery, [26] Electricity, [27] Hot conditions (natural origin, includes sunlight), [28] Cold conditions (natural origin), [29] Other specified external cause, [30] Unspecified external cause.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…All emergency presentations where "injury cause" had been recorded were included in the study. Injury cause included the following categories (code description): [1] Motor vehicle -driver, [2] Motor vehicle -passenger, [3] Motorcycle -driver, [4] Motorcycle -passenger, [5] Pedal cyclist -rider or passenger, [6] Pedestrian, [7] Horse related (fall from, struck or bitten by), [8] Other transportrelated circumstance, [9] Fall -low (same level or less than 1 metre, or no information on height), [10] Fallhigh (greater than 1 metre), [11] Submersion or drowning -swimming pool, [12] Submersion or drowning -other, [13] Other threat to breathing (includes strangulation and asphyxiation), [14] Fire, flames and smoke, [15] Scalds (hot drink, food, water, other fluid, steam, gas or vapour), [16] Contact burn (hot object or substance), [17] Poisoning -medication, [18] Poisoning -other or unspecified substance, [19] Firearm, [20] Cutting and piercing object, [21] Dog related, [22] Other animal related, [23] Struck by or collision with person, [24] Struck by or collision with object, [25] Machinery, [26] Electricity, [27] Hot conditions (natural origin, includes sunlight), [28] Cold conditions (natural origin), [29] Other specified external cause, [30] Unspecified external cause.…”
Section: Data Sourcesmentioning
confidence: 99%
“…[1][2][3] Injuries in the agricultural workforce can be severe due to the types of exposures, requiring significant time off work and potentially leading to death, psychological trauma or permanent disability. 1,[4][5][6] A report from SafeWork Australia showed that agriculture had the highest rates of injury across all industries in 2019 and consequently has been identified as a priority industry for prevention strategies. 3 In addition, agricultural workers (including farmers, farm managers and farm workers) often continue to perform farm-related tasks past the age of retirement due to financial concerns, a desire to maintain independence and productivity, and a perception of retirement as a major change to their identity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Six percent of the Irish workforce is employed in agriculture, but the sector accounts for 40% of workplace fatalities. 11 Data for New Zealand tell a similar tale, with the agriculture, forestry and fishing industries having a high injury claim rate of 190 claims per 1000 fulltime equivalent workers (FTE) in 2018. 6,13 Work-Safe data show there were 28 agricultural fatalities during the 2012-18 year period in the Midland region.…”
Section: Introductionmentioning
confidence: 97%
“…6 Australia, Ireland, Canada and the United Kingdom all report agriculture as one of their most hazardous industries, with considerable costs to individuals, their families and farms due to injury. [7][8][9][10][11][12] Australian estimates suggest that farm injuries account for 17% of all worker deaths, and farm injuries occur at a rate of 56.4 per 1000 workers. 3 Six percent of the Irish workforce is employed in agriculture, but the sector accounts for 40% of workplace fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 90's studies in Poland and Romania, reported horse-cart accidents were among the leading causes of SCI [12,13]. Livestock and machineryrelated TSCIs may have been reported in rural farming communities in Ireland and India [14]. In Asia for instance, ladies' long scarves become caught in rickshaw wheels and other machineries causing cervical SCIs [12].…”
Section: Introductionmentioning
confidence: 99%